Konsep "Bapa'Babu'Guru Raton" pada Masyarakat Madura sebagai Wujud Pengalaman Sila ke-2 Pancasila - Ridwan Ahmad Sukri (Jurnal Filsafat "WISDOM", 1999)
This research is on Maduranese the concept of Bapa 'Babu' guru rato as a realization of second princple of Pancasila. That concept means the good relationship between some one to his parents, teachers, and goverment. As a part of value system, it also influenced by the concrete conducts because of its imperative characteristic.The main probelm laid down in how the realization of that value to day is. The researcher compared between the ideal values Bapa "Babu" guru rato its concrete forms in daily activity.The research was conducted by studying literature and data collected from primary and secondary source, which have been published or not. Interpretation, induction-deduction, comparation, and description method were in the analysis of the data. Conclusion is made based on logical thinking.The result of this work is that Maduranese has wltanschauung, way of life, which derrived from both individual and social aspects. Social aspects are not, only better and bigger than individualistic one but also there is collaboration with self-honor, principles of democracy, respecting to any others aforementioned. There are concretization and realization of second princple of Pancasila that is meant.